A newly assigned role of ctcf in cellular response to broken dnas - Kang, Mi Ae; Lee, Jong Soo (Biomolecules, 2021)
Best known as a transcriptional factor, CCCTC-binding factor (CTCF) is a highly conserved multifunctional DNA-binding protein with 11 zinc fingers. It functions in diverse genomic processes, including transcriptional activation/repression, insulation, genome imprinting and three-dimensional genome organization. A big surprise has recently emerged with the identification of CTCF engaging in the repair of DNA double-strand breaks (DSBs) and in the maintenance of genome fidelity. This discovery now adds a new dimension to the multifaceted attributes of this protein. CTCF facilitates the most accurate DSB repair via homologous recombination (HR) that occurs through an elaborate pathway, which entails a chain of timely assembly/disassembly of various HR-repair complexes and chromatin modifications and coordinates multistep HR processes to faithfully restore the original DNA sequences of broken DNA sites. Understanding the functional crosstalks between CTCF and other HR factors will illuminate the molecular basis of various human diseases that range from developmental disorders to cancer and arise from impaired repair. Such knowledge will also help understand the molecular mechanisms underlying the diverse functions of CTCF in genome biology. In this review, we discuss the recent advances regarding this newly assigned versatile role of CTCF and the mechanism whereby CTCF functions in DSB repair.
Keywords: Animals; CCCTC-Binding Factor; DNA Breaks, Double-Stranded; DNA Repair; Homologous Recombination; Humans; Models, Biological; Promoter Regions, Genetic; CTCF; DNA damage repair; Homologous recombination